The fear of COVID-19 outbreak among health care professionals in Gaza Strip, Palestine. (June 2021) - Shehada, Ameer Khalil; Albelbeisi, Ahmed Hassan; Albelbeisi, Ali; El Bilbeisi, Abdel Hamid; El Afifi, Amany
Introduction: The emergence of the COVID-19 and its consequences has led to fears, worries, and anxiety among individuals, particularly among healthcare professionals. The present study aimed to assess the fear of COVID-19 among different healthcare professionals in the Gaza Strip, Palestine. Methods: A cross-sectional, snowball sampling technique and an online questionnaire were employed among healthcare professionals. A total of 300 participants completed the questionnaire. The validated fear of COVID-19 Scale Arabic version was used. Statistical analysis was performed using SPSS version 22. Results: The sample fear mean score was 17.53 ± 5.78; more than half of the study participants (54.3%) consider it as low levels of fear and 45.7% of the participants consider it as high levels of fear. Statistically significant differences were found between males and females, and different healthcare professional's disciplines. Females have a higher mean score compared to males. The highest fear mean scores were found among Lab-Technicians (20.19 ± 7.42), followed by X-ray-Technicians (17.95 ± 3.96), Nurses (17.1 ± 5.55), and Physicians (16.25 ± 4.66). Conclusion: The fear of COVID-19 was high among female healthcare professionals compared to males, as well as, among Lab-Technicians compared to Physicians and Nurses. There is a need to establish a strategy to continues measuring the psychological effect of COVID-19 among healthcare professionals especially females.